2006
DOI: 10.1051/animres:2006039
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbohydrases in corn-soybean meal based grower-finisher pig diets

Abstract: -Four experiments were conducted to determine the effects of carbohydrase (CS) supplements in pig diets on ileal digestibility and ammonia emission. The CS used in this study is composed of the enzymes obtained from Aspergillus niger and Aspergillus oryzae during their fermentation process. The major active enzymes were α-1,6-galactosidase, β-1,4-mannanase, and β-1,4-mannosidase that target flatulence producing compounds in soybean meals. In experience 1 (Exp. 1), 8 cannulated barrows (93.9 ± 2.0 kg) were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
3
18
0
4
Order By: Relevance
“…Kim et al (2006), Wang et al (2009), and Ao et al (2010) also reported increases in digestibility as a result of β-mannanase supplementation. In contrast, Pettey et al (2002) reported no change in nutrient digestibility as a result of β-mannanase supplementation.…”
Section: Discussionmentioning
confidence: 87%
“…Kim et al (2006), Wang et al (2009), and Ao et al (2010) also reported increases in digestibility as a result of β-mannanase supplementation. In contrast, Pettey et al (2002) reported no change in nutrient digestibility as a result of β-mannanase supplementation.…”
Section: Discussionmentioning
confidence: 87%
“…, trabalhando com adição de complexo enzimático (α-1,6-galactosidase, β-1,4-mananase, β-1,4-manosidase) em dietas à base de milho e farelo de soja, e não casca de soja, para leitões na fase inicial (11,05 kg), verificaram diminuição significativa da concentração de rafinose e estaquiose durante a passagem pelo intestino delgado com o uso dessas enzimas. Estudando o efeito do mesmo complexo enzimático sobre a digestibilidade de dietas à base de milho e farelo de soja para suínos, Kim et al (2006) verificaram melhora na digestibilidade ileal da matéria seca e energia bruta com o nível de 0,05% de suplementação enzimática.…”
Section: Resultsunclassified
“…Esse resultado pode estar relacionado à ação do complexo enzimático sobre os oligossacarídeos e PNA presentes na casca de soja e no farelo de soja, que reduzem o desempenho. Esse resultado foi semelhante aos obtidos por , que trabalharam com adição de 0,10% de complexo enzimático (α-1,6-galactosidase, β-1,4-mananase, β-1,4-manosidase) em dietas à base de milho e farelo de soja para leitões com peso inicial médio de 11,05 kg durante um período Kim et al (2006), utilizando complexo enzimático (composto por α-1,6-galactosidase, β-1,4-mananase, β-1,4-manosidase), 0,05%, para suínos com peso médio de 24,1 kg, durante quatro semanas, não observaram efeito sobre o consumo de ração, o ganho de peso e a conversão alimentar. Contudo, esses mesmos autores, utilizando animais mais pesados, com peso médio inicial de 64,1 kg, observaram melhora apenas para o ganho de peso.…”
Section: Resultsunclassified
“…Balancing diets for these animals is challenging since meal supplements high in protein and oils, such as guar, soya, palm and coconut kernel meals cannot be included in large quantities due to detrimental effects, such as poor digestion (sticky droppings) in chicken and flatulence in pigs, due to their inability to degrade or use the mannans or MOS present in these meals [108][109][110]. Treatment of these high mannancontaining meals with ␤-mannanases has shown improved body weight gain in broiler chickens, as well as overcoming flatulence in pigs [109,110].…”
Section: Animal Feedsmentioning
confidence: 99%